Interleukin–33, Oxidative Stress in Prediabetic Polycystic Ovary Syndrome Patients with Insulin Resistance - Al-Taie, Wafa F.; AL-Rubaei, Zainab M.; Hassan, Abeer Jabbar (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Polycystic ovary syndrome (PCOS) is one of the common female endocrine disorders of uncertain etiology, which causes menstrual disorders as well as infertility. Interleukin–33(IL-33) is considered as a strong risk marker of inflammation and may have possible role in pathogenesis of PCOS.Objectives: The present study is designed to investigate the possible role of IL-33 in pathogenesis of PCOS and its relation with glycated hemoglobin (HbA1C),insulin resistance(IR) and oxidative stress in prediabetic PCOS patients.Subjects and Methods: The study involved 30 healthy women as control group and sixty six infertile Iraqi women with PCOS which were divided into two groups according to glycated heamoglobin(HbA1c) value and homeostasis model assessment for insulin resistance (HOMA-IR). The first group (G1) consist of 30 women with HbA1c ≤ 6.5% and HOMA –IR